Pharmacological Inhibition of Ferroptosis as a Therapeutic Target for Neurodegenerative Diseases and Strokes - Wang, Yumin; Wu, Shuang; Li, Qiang; Sun, Huiyan; Wang, Hongquan (Advanced science, 2023)
Emerging evidence suggests that ferroptosis, a unique regulated cell death modality that is morphologically and mechanistically different from other forms of cell death, plays a vital role in the pathophysiological process of neurodegenerative diseases, and strokes. Accumulating evidence supports ferroptosis as a critical factor of neurodegenerative diseases and strokes, and pharmacological inhibition of ferroptosis as a therapeutic target for these diseases. In this review article, the core mechanisms of ferroptosis are overviewed and the roles of ferroptosis in neurodegenerative diseases and strokes are described. Finally, the emerging findings in treating neurodegenerative diseases and strokes through pharmacological inhibition of ferroptosis are described. This review demonstrates that pharmacological inhibition of ferroptosis by bioactive small‐molecule compounds (ferroptosis inhibitors) could be effective for treatments of these diseases, and highlights a potential promising therapeutic avenue that could be used to prevent neurodegenerative diseases and strokes. This review article will shed light on developing novel therapeutic regimens by pharmacological inhibition of ferroptosis to slow down the progression of these diseases in the future. The roles of ferroptosis contributing to neurodegenerative diseases and strokes are described, and the emerging data in treating these diseases through pharmacological inhibition of ferroptosis, highlighting a potential promising therapeutic avenue that could be used to prevent neurodegenerative diseases and strokes are summarized. This review will shed light on developing novel therapeutic regimens through inhibiting ferroptosis to slow down the progression of these diseases in the future.